Relationship between Stature and Length of Tendo Achilles in Adult Male and Female of Bangladesh - Amin, Sanjida; Ara, Shamim; Naznin, Rawshon; Marium, Umma; Diba, Farah; Amin, Fatima (Delta Medical College Journal, 2020)
Background: Tendo Achilles injuries are usually related to poor ankle flexibility and strength and to overuse. Morphology of tendo Achilles is an important tool for its assessment which can be done by measuring tendon thickness, cross-sectional area and length of tendon. Objective: The aim of the study was to correlate length of tendo Achilles with stature in several age groups of sedentary people as measured by ultrasonography. Materials and method: This cross sectional analytical type of study was conducted in the department of Anatomy, Dhaka Medical College Hospital, Dhaka, Bangladesh from July 2013 to June 2014. The present study was performed on 200 tendo Achilles of 100 people (50 male and 50 female) randomly selected from the patients who came to the Radiology department of Dhaka Medical College Hospital for ultrasonography of any region of their body other than leg. Results: In this study length of tendo Achilles was measured in both legs of adult people and was correlated with stature. Highly significant correlation was found between length of tendo Achilles with stature (p<0.001). Conclusion: The data of length of tendo Achilles obtained from the present study may provide valuable information in different aspects of medical science as a guide line for physiotherapists, radiologists, sports professionals and ortho-surgeons in early detection and monitoring of rehabilitation especially of professional athletes. Delta Med Col J. Jul 2019 7(2): 80-83